PKM Pengolahan Kain Perca Bagi Ibu Masyarakat Desa Munggugianti, Kec. Benjeng, Kab. Gresik: indonesia - Utami, Christina Whidya; Sumaji, Yoseva Maria Pujirahayu; Bramantyo, Paskalis Dio; Syahrin, Nabila Aurelia (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The Community Partnership Program (PKM) entitled "PKM Patch Fabric Processing for Mothers of the Munggugianti Village Community, Kec. Benjeng, Kab. Gresik” aims to solve the problems faced by partner (a group of patchwork craftsmen in Munggugianti Village, Benjeng District, Gresik Regency). The problems faced by PKM partners cover 4 aspects, namely: a) Development of the patchwork craftsman business, b) Innovation of patchwork processing, c) Marketing of processed patchwork products, d) Administration and finance of the patchwork craftsman business. Solutions to business development difficulties offered by PKM to partners include: 1) Efforts to provide basic business knowledge, 2) Provision of basic business development modules, 3) Providing basic business training. Innovative Solutions for Patchwork Processing, completed by: 1) training on making standardized patchwork handicraft products 2) Socialization on the introduction of types of patchwork processed products. Solution to the third problem (Marketing of Processed Patchwork Products) by: 1) Equipping participants with the knowledge of promoting a product, 2) Introducing marketing channels, 3) opening marketing through online and offline channels. The solution to the fourth problem (Administration and financial business) is achieved through: 1) introducing financial institutions, 2) Providing training on the basics of financial business. The process of implementing the PKM program is carried out through approach methods, partner participation and an evaluation process for the activities that have been held. The outputs of the Community Partnership Program (PKM) are in the form of: 1) publication of articles in nationally accredited journals or national proceedings, 2) Improvement and understanding of the management capabilities of partners (patchwork craftsmen), 3) Increase in the income of patchwork craftsmen from the business they run, 4) Have patchwork processed products that are ready to be marketed.